Social and Economic Perspective of Dink Culture and it’s Impact on Indian Economy - T N Geetha (Journal of Management and Science, 2025)
DINK household’s couples with a double income and no children have increased dramatically during the last few decades. The DINK lifestyle has gained popularity, despite initially appearing in the 1980s amid a recession when the expenses of raising children skyrocketed. Research on the economic influence of the childless population is summarized in this publication. To demonstrate the disproportionate influence of DINKs, it compiles information on earnings, savings rates, spending patterns, and consumer preferences. Their decisions will probably change economies, particularly in service industries like dining and travel. To combat aging populations, governments may, nevertheless, implement legislative changes that encourage childbearing. Changing cultural norms are reflected in the development of DINKs, which presents both opportunities and difficulties. Their financial clout will only increase in the upcoming years. Voluntary childlessness is on the rise as marriage and pregnancy rates fall in affluent nations. The term "double income, no kids," or DINK, is a novel concept in the social sphere that is becoming more and more popular among young married couples worldwide. According to DINK couples, having no children means having more money to spend. This implies that such funds could be used for the couple’s personal enjoyment and social advancement. Over time, women have become more financially literate. They have scared attachment patterns and would rather invest their money than use it to raise children. Additionally, the findings suggest that glamping might be used as a venue for couples’ counseling and to commemorate important occasions enhance close relationships.